2004
DOI: 10.1016/s1074-7613(04)00080-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune Sensitization in the Skin Is Enhanced by Antigen-Independent Effects of IgE

Abstract: Contact sensitivity responses require both effective immune sensitization following cutaneous exposure to chemical haptens and antigen-specific elicitation of inflammation upon subsequent hapten challenge. We report that antigen-independent effects of IgE antibodies can promote immune sensitization to haptens in the skin. Contact sensitivity was markedly impaired in IgE(-/-) mice but was restored by either transfer of sensitized cells from wild-type mice or administration of hapten-irrelevant IgE before sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
177
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(191 citation statements)
references
References 52 publications
12
177
1
1
Order By: Relevance
“…However, identifying and characterizing specific immunomodulatory roles of mast cells during particular immune responses in vivo may be quite challenging. For example, it already is clear that mast cells can have either positive or negative immunomodulatory functions in what would appear to be very similar settings, such as in different mouse models of CHS that employ different types and/or concentrations of haptens and/or different vehicles for administering these haptens 5,13,60,87,88 (Figure 3). One may even speculate that in immune responses in which mast cells first promote the sensitization phase of the response, mast cells could then help to initiate the local inflammation that occurs when the host is subsequently exposed to specific antigen, and finally help to limit the extent of, and/or resolve, the ensuing inflammation and associated tissue pathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying and characterizing specific immunomodulatory roles of mast cells during particular immune responses in vivo may be quite challenging. For example, it already is clear that mast cells can have either positive or negative immunomodulatory functions in what would appear to be very similar settings, such as in different mouse models of CHS that employ different types and/or concentrations of haptens and/or different vehicles for administering these haptens 5,13,60,87,88 (Figure 3). One may even speculate that in immune responses in which mast cells first promote the sensitization phase of the response, mast cells could then help to initiate the local inflammation that occurs when the host is subsequently exposed to specific antigen, and finally help to limit the extent of, and/or resolve, the ensuing inflammation and associated tissue pathology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bryce et al (48) have shown that mast cells are required for contact sensitivity and dendritic cell reduction in the epidermis following hapten exposure. However, our results indicate that LC migration to draining LNs can be induced by IgE-mediated mast cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies using genetically mast cell-deficient mice have shown that mast cells can promote the migration of Langerhans cells from the epidermis upon hapten sensitization in a model of oxazolone-induced contact hypersensitivity (6) and that the IgEand Ag-dependent activation of skin mast cells can promote the migration of skin DCs to local draining lymph nodes by a mechanism that is in part H 2 histamine receptor-dependent (7).…”
Section: Ast Cells Represent Important Effector Cells In Th2-andmentioning
confidence: 99%
“…We tested three populations of BMCMCs by FACS analysis: nonsensitized (naive), IgE-sensitized, and IgE-and Ag-stimulated (IgE/Ag), because we and other investigators have reported evidence that occupancy (and perhaps cross-linking) of the high affinity IgE receptor, Fc⑀RI, by IgE alone can enhance mast cell survival and/or function (6,32,33). We found that naive BMCMCs from C57BL/6J, WB ϫ B6 F 1 hybrid, or BALB/cKa mice did not express detectable levels of MHC class II (I-A) molecules on their cell surface (No IgE cells in Fig.…”
Section: Expression Of Members Of the B7 And Cd28 Families Of Costimumentioning
confidence: 99%